Associations between water insecurity and depression among refugee adolescents and youth in a humanitarian context in Uganda: cross-sectional survey findings - Logie, Carmen H; Okumu, Moses; Loutet, Miranda; Berry, Isha; Taing, Lina; Lukone, Simon Odong; Kisubi, Nelson; Sokolovic, Nina; Kyambadde, Peter (International Health, 2023)
ABSTRACT Background Water insecurity is linked to poor mental health through intrapersonal, relational and community-based stressors. We examined water insecurity and depression among refugee youth in Bidi Bidi, Uganda. Methods We conducted a cross-sectional survey and multivariable ordinal logistic regression to examine associations between water insecurity and depression severity, adjusting for gender, resilience, social support and food insecurity. Results Among participants (n=115; mean age: 19.7 y, SD 2.3), 80.0% reported water insecurity and 18.3% had moderate/severe depression symptoms. Water insecurity was independently associated with higher levels of depression severity (adjusted OR: 5.61; 95% CI 1.20 to 26.30; p=0.03). Conclusions Findings suggest water insecurity was commonplace and associated with depression. Water insecurity could be integrated in refugee mental health promotion by policymakers and community-based programmers.